IDENTIFIKASI CEPAT MIKROORGANISME MENGGUNAKAN ALAT VItEK-2 - prihatini .; aryati .; hetty . (Indonesian Association of Clinical Pathologist and Medical laboratory, 2007)
Vitek-2 is automatic microbiologic equipment which used to identify antimicrobial sensitivity by micro organism test have been launched in Indonesia. In some private laboratory and hospital this equipment has been used already. The purpose of this study is toknow how to operate this equipment to ID and AST as well as to compare with the conventional methods. The material used to test withthis equipment consist of pure colony culture which derived by suspension of one inoculation to ID or AST card. The reagent consistsonly of saline suspension. After the suspension installed to VITEK2, the result was verified in the printout about 1.5 hours. The colour ofID and AST is difference and couldn’t change with each other. The results are appear more rapid than the others conventional methods.VITEK-2 can be used as a means to diagnose faster than the conventional methods., so that the physician could prescribe earlier as soonas possible to patients and reduced the hospital budgets as well.